1976
DOI: 10.1037/0097-7403.2.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Long-term interference effect: An alternative to learned helplessness.

Abstract: This article presents three experiments that explore whether inescapable shock of long duration and moderate intensity (LoShk) produces an avoidance-escape deficit (called an interference effect) by causing animals to learn to respond less actively or by causing them to learn to be "helpless."The first experiment showed that if animals given LoShk were subsequently tested in an avoidance-escape "nosing" response that required little motor activity, they learned and performed better than no-shock controls. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(67 citation statements)
references
References 18 publications
(47 reference statements)
3
56
1
7
Order By: Relevance
“…These two characteristics define the phenomenon known as learned helplessness. In the original experiment (Seligman & Maier, 1967; for reviews see Maier & Jackson, 1979, Alloy & Seligman, 1979and Glazer & Weiss, 1976) dogs were first restrained in a harness and given a series of severe, inescapable shocks. The next day, they were placed in a simple discriminated avoid-ance situation: in each trial, when a CS came on, shock followed after ten seconds unless the dogs jumped over a low barrier.…”
Section: Avoidance and Escapementioning
confidence: 99%
“…These two characteristics define the phenomenon known as learned helplessness. In the original experiment (Seligman & Maier, 1967; for reviews see Maier & Jackson, 1979, Alloy & Seligman, 1979and Glazer & Weiss, 1976) dogs were first restrained in a harness and given a series of severe, inescapable shocks. The next day, they were placed in a simple discriminated avoid-ance situation: in each trial, when a CS came on, shock followed after ten seconds unless the dogs jumped over a low barrier.…”
Section: Avoidance and Escapementioning
confidence: 99%
“…It hasbeen termed the leamed helplessness effect (Seligman, 1975) or the interference effect (Glazer & Weiss, 1976a, 1976b. The learned helplessness theory (Maier & Seligman, 1976;Seligman, 1975) explains that this effect arises from the leaming of uncontrollability-that outcomes are independent of responses.…”
mentioning
confidence: 99%
“…However, stressor-induced al terations in avoidance behavior are not always evident immediately following exposure to stressors. For exam ple, inescapable footshock produces deficits in shuttle escape performance 24-72 h after exposure to shock but escape deficits are typically not evident immediately fol lowing shock (Anisman 1975;Glazer and Weiss 1976;Anisman et al 1978;Prince and Anisman 1984). It is therefore possible that footshock can alter amphetamine-CTA but only when footshock precedes saccharin-am phetamine pairing by 24-72 h. Experiment 2 was con ducted to evaluate the impact of exposure to footshock a number of days prior to saccharin-amphetamine pair-T ab le 1 M ean (±SEM) water consumption values (ml) on days prior to (Baseline) and between saccharin consumption tests for the four treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why the facilitation of amphetamine-CTA is not evident when shock is applied between saccharin consumption and amphetamine injec tions but there are other examples of the delayed effects of stressors on avoidance responses. For example, stressinduced deficits in shuttle escape responding are typical ly not evident immediately following stressor exposure but are evident 24 or 48 h later (Anisman 1975;Glazer and Weiss 1976;Anisman et al 1978;Prince and Anis man 1984;Anisman and Zacharko 1988). Studies exam ining cross-sensitization between stressors and stimu lants like amphetamine have also shown that cross-sensi tization usually requires a delay between stressor expo sure and stimulant exposure (Ante]man et al 1983;Rob inson and Becker 1986).…”
Section: Discussionmentioning
confidence: 99%